IMPLEMENTASI NILAI TASYRI' AL-QUR'AN DALAM PENDIDIKAN ANAK - Riri Afriani Nasution; Azura Chaisa Kirana; Muhammad Ramadhani Suheri; Aryo Wijaya; Bayu Andriyan (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the legislative miracle (i'jaz tasyri') of the Qur'an as a universal and adaptive legal system capable of addressing the changing dynamics of human society. The research employed a qualitative approach using library research by examining ayat al-ahkam (legal verses), classical and contemporary Qur'anic commentaries, and relevant scholarly literature. A descriptive analysis was conducted to identify the distinctive characteristics of Qur'anic legislation compared with human-made legal systems. The findings indicate that Islamic law integrates the principles of justice, public welfare (maslahah), maqasid al-shari'ah, and a balance between immutable principles (tsawabit) and flexible provisions (mutaghayyirat). These principles are reflected in regulations concerning inheritance, marriage, and commercial transactions, which contribute to social stability, protection of rights, and the establishment of a just social order across different contexts and periods. The study concludes that i'jaz tasyri' demonstrates the enduring relevance and superiority of the Qur'anic legal system in responding to the evolving needs of humanity.